Diagnostic Accuracy of Different Methods in Detecting Factor V Leiden Mutation in Tertiary Care Centre - Barlas, Sidra; Robert, Helen Mary; Mahmood, Asad; Mahmood, Rafia; Khurshid, Ayesha; Khan, Saleem Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of clotting based APCR assay in determining Factor V Leiden mutation with PCR as gold standard and to establish the frequency of factor V Leiden mutation in patients presenting with thrombophilia as well as to study their clinical presentations and association with arterial or venous thrombosis. Study Design: Cross sectional study. Place and Duration of Study: Army Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Dec 2018 to Sep 2019. Methodology: A total of 230 patients were recruited which presented with DVT and other thrombotic conditions. Acquired causes of Factor V Leiden mutation were excluded from our study. For Screening tests APCR, blood was collected in 3.2% sodium citrate tubes while for PCR blood was collected in K2 EDTA tubes. Results: On Screening, APCR test 44 (19.29%) showed positive results with cut-off value of <0.8 while 184 (80.70%) were negative. Out of total 230 patients, Factor-v mutation was detected in 42 (18.4%) of patients. On statistical analysis, Screening APCR was found to be 95.45% (95% sensitive CI: 83.84%-99.42%) and 97.85% (95%CI: 94.59%-99.41%) specific as compared to our gold standard method PCR. The positive likelihood ratio was 44.39 (95%CI: 16.76-117.03) while the negative likelihood ratio was 0.05 (95%CI: 0.01-0.19) with a positive predictive value and a negative predictive value of 91.30% (95% CI: 79.10%- 96.35%) and 98.91% (95%CI: 95.92%-99.72%), respectively. The accuracy was 97.39% (95% CI: 94.36%-99.03%). Conclusion: APCR for Factor-v Leiden Screening is a rapid and cost-effective method for diagnosis of Factor-v Leiden mutation.